Social success, life story and formation of a woman the rural - Francinilda Honorato dos Santos; Ana Lúcia Oliveira Aguiar; Stenio de Brito Fernandes (Universidade Federal do Norte do Tocantins, 2022)
This study aims to understand how a woman the rural achieved social success through studies in her life and formation history, in dialogue between the knowledge of experience and academic knowledge. It is a research with a qualitative approach, developed from the theoretical contribution of the (auto)biographical method with a focus on the narratives on of a woman the rural. We point out that the teacher's contributions as a thinker and intellectual that guides the discussions about the experiences of women in the rural, and the educational dimensions, (re)signified the memories of the woman in rural and reconstructed the senses of her educational practice and formative experiences in relationship with the other in his successful trajectory of studies for his academic formation, providing (auto)knowledge and, then, (auto)formation. This is one of the possibilities to demonstrate the relevance of life stories of simple people to understand the importance of dialogue, in the social sphere, of knowledge and life trajectories of rural women. Their struggles, their achievements, their life trajectories can be added to make society rethink about projects and actions, which are related to their insertion in education and other social dimensions.